Analysis of parental communication and sexual risk behavior among adolescents based on gender - Harahap, Yanna Wari; Nurlaila, Nurlaila; Harahap, Irawati; Antoni, Adi; Hasibuan, Ahmad Safii; Suryati, Suryati (Institute of Computer Science (IOCS), 2025)
Adolescents are a group that is highly vulnerable to risky sexual behaviors. One of the factors influencing such behaviors is communication between parents and children. Good communication can serve as a protective factor against unhealthy sexual behavior. This study aims to analyze the influence of parent–child communication on risky sexual behavior among adolescents, as well as its differences based on gender. The study employed an analytical quantitative design with a cross-sectional approach. The sample consisted of 120 male and female adolescents selected through proportional random sampling. Data were collected using standardized questionnaires that had been tested for validity and reliability. Analysis was conducted using Pearson correlation and Independent t-test with a significance level of 0.05. The results showed a significant negative correlation between parental communication and risky sexual behavior (r = –0.65; p < 0.001). The better the communication between parents and adolescents, the lower the level of risky sexual behavior. Gender differences were also observed, where female adolescents demonstrated higher communication scores and lower risky sexual behavior compared to males (p < 0.001). Effective communication between parents and children plays a crucial role in preventing risky sexual behaviors among adolescents. Strengthening family communication through reproductive health education programs involving active parental participation is essential.